Realization of Robust and Precise Regulation of Gene Expression by Multiple Sigma Recognizable Artificial Promoters - Han, Laichuang; Chen, Qiaoqing; Lin, Qiao; Cheng, Jintao; Zhou, Li; Liu, Zhongmei; Guo, Junling; Zhang, Linpei; Cui, Wenjing; Zhou, Zhemin (Frontiers in Bioengineering and Biotechnology, 2020)
Precise regulation of gene expression is fundamental for tailor-made gene circuit design in synthetic biology. Current strategies for this type of development are mainly based on directed evolution beginning with a native promoter template. The performances of engineered promoters are usually limited by the growth phase because only one promoter is recognized by one type of sigma factor (σ). Here, we constructed multiple-σ recognizable artificial hybrid promoters (AHPs) composed of tandems of dual and triple natural minimal promoters (NMPs). These NMPs, which use σA, σH and σW, had stable functions in different growth phases. The functions of these NMPs resulted from an effect called transcription compensation, in which AHPs sequentially use one type of σ in the corresponding growth phase. The strength of the AHPs was influenced by the combinatorial order of each NMP and the length of the spacers between the NMPs. More importantly, the output of the precise regulation was achieved by equipping AHPs with synthetic ribosome binding sites and by redesigning them for induced systems. This strategy might offer promising applications to rationally design robust synthetic promoters in diverse chassis to spur the construction of more complex gene circuits, which will further the development of synthetic biology.